Tumor treating fields: a new treatment for glioblastoma - Dimitar Slavkov; Asen Hadzhiyanev; Svetoslava Slavkova (Biotechnology & Biotechnological Equipment)
Glioblastoma (GBM) is a fatal type of brain tumour. According to the World Health Organization (WHO) classification of 2021, GBMs have WHO grade 4 and are usually associated with a poor prognosis. Since GBMs show a pronounced infiltrative growth, a cure by complete resection of the tumor is unfortunately not possible. Both systemic and locoregional therapy methods are traditionally used and tested to improve the prognosis. A new method that is intended to prolong the progression-free survival is using electromagnetic alternating fields, the so-called tumor treating fields (TTF). This method is based on alternating electrical fields that act on the shaved scalp. The aim is to disrupt cell division and organization of cell organelles. In this review, we discuss the mechanism of TTF, summarize the results of our comprehensive literature search, and discuss potential of this new anti-cancer treatment modality.